Rock weathering creates oases of life in a high arctic desert - S. Borin; F. Tambone; F. Mapelli; L. Brusetti; B. Scaglia; R. Marasco; F. Adani; D. Daffonchio; S. Ventura; F. Schubotz; L. P. D'Acqui; B. Solheim; et al. (Environmental Microbiology, 2010)
During primary colonization of rock substrates by plants, mineral weathering is strongly accelerated under plant roots, but little is known on how it affects soil ecosystem development before plant establishment. Here we show that rock mineral weathering mediated by chemolithoautotrophic bacteria is associated to plant biocenosis formation in sites recently released by permanent glacier ice cover in the Midtre Lovénbreen glacier moraine (78°53’N), Svalbard. Increased soil fertility fosters growth of prokaryotes and plants at the boundary between sites of intense acidithiobacilli-mediated chemolithotrophic iron-sulfur oxidation, and the common moraine substrate where carbon and nitrogen are fixed by cyanobacteria. Acidithiobacillus ferrooxidans activity determines acidity and corresponding fertility gradients, where water retention, cation exchange capacity and nutrient availability are increased. This fertilization is enabled by abundant mineral nutrients and reduced forms of iron and sulfur in pyrite stocks within a conglomerate type of moraine rock. Such an interaction between microorganisms and moraine minerals determines a peculiar, not yet described model for soil genesis and crop formation with potential past and present analogues in other harsh environments with similar geochemical settings.